Mucous retention cyst in maxillary sinus with expansion of maxillary tuberosity: case Report - Mattos, Renato Garcia; Egas, Lais Sara; Oliveira, Priscila Carneiro; Bassi, Ana Paula Farnezi; Souza, Francisley Avila; Ponzoni, Daniela (Journal of Oral Diagnosis, 2018)
Mucosal retention cyst in the maxillary sinus is a benign entity that results from obstruc- tion and dilation of seromucous glands ducts due to inflammation, infection or reaction of maxillary sinus mucosa to allergic processes. It is an asymptomatic lesion, usually identified in routine imaging tests requested by professionals. The present study aims to present a case of maxillary sinus mucosal retention cyst in a 63 years old patient who reported difficulty in adapting her total upper prosthesis and persistent pain in the left maxilla. The treatment was surgical enucleation.